Pengembangan e-LKM Terintegrasi Literasi Numerasi untuk Meningkatkan Berpikir Kritis pada Materi Analisis Vektor - Peni, Nur Robiah Nofikusumawati; Sumargiyani, Sumargiyani; Prasetyo, Puguh Wahyu (Jurnal Tadris Matematika, 2023)
Students' low reading interest greatly affects learning outcomes in Vector Analysis class. This is due to the rare interaction between students and learning resources in class. To increase student activity in reading and understanding the concept of vector analysis material, an e-LKM product is needed. This study aims to develop Student Worksheets (LKM) in electronic form that is integrated with numeracy literacy which can be used for learning vector analysis courses by knowing the validity and practicality of procedures so that the use of these e-LKM can improve students' critical thinking. This development research uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Furthermore, the evaluation stage is carried out at each stage to improve the e-LKM that is made. The subjects were 21 students in semester VI of class C Mathematics Education FKIP Universitas Ahmad Dahlan. The research data was obtained by collecting questionnaires from material experts, media, and students' responses to the practicality of the media being developed. From the results of the questionnaires distributed, the average questionnaire from the two material experts and media experts showed excellent criteria with a mean score of 4.611 and 4.47 respectively. The results of student responses to product use show excellent criteria with a mean score of 4.27. Based on these results, the e-LKM that is used is proven to be valid and practical.